Pengaruh Market Day Terhadap Literasi Keuangan dan Kemampuan Berpikir Simbolik Anak Usia 5-6 Tahun: The Effect of Market Day on Financial Literacy and Symbolic Thinking Skills in 5-6 Year Old Children - Sri Idamulyani; Bachri, Bachtiar Sjaiful; Khotimah, Nurul (Universitas Ngudi Waluyo, 2024)
This study aims to determine the effectiveness of market day activities in improving financial literacy and cognitive abilities of symbolic thinking in children aged 5-6 years. This study used an experimental design with two groups: an experimental group that participated in market day activities and a control group that did not participate in these activities. Data were collected through financial literacy and symbolic thinking cognitive ability tests before and after the intervention. Data were analyzed using SPSS, including paired t-test and unpaired t-test. The results showed that there were significant improvements in financial literacy and symbolic thinking cognitive ability in the experimental group compared to the control group. The average financial literacy score in the experimental group increased from 56.78 to 76.45, while in the control group it only increased from 57.12 to 60.89. This increase was significant based on paired t-test (p < 0.05) and unpaired t-test (t = 4.56, p < 0.05). Similarly, the average score of symbolic thinking cognitive ability in the experimental group increased from 58.34 to 80.23, while in the control group it only increased from 58.67 to 62.45. This increase was also significant based on paired t test (p < 0.05) and unpaired t test (t = 5.34, p < 0.05). Based on this research, it shows that market day activities are effective in improving financial literacy and cognitive abilities of symbolic thinking of children aged 5-6 years. Thus, this activity is recommended to be integrated into the early childhood education curriculum. Further research is needed to explore the long-term impact and effectiveness of this activity in different age groups. ABSTRAK Penelitian ini bertujuan untuk mengetahui efektivitas kegiatan market day dalam meningkatkan literasi keuangan dan kemampuan kognitif berpikir simbolik pada anak usia 5-6 tahun. Penelitian ini menggunakan desain eksperimen dengan dua kelompok: kelompok eksperimen yang mengikuti kegiatan market day dan kelompok kontrol yang tidak mengikuti kegiatan tersebut. Data dikumpulkan melalui tes literasi keuangan dan kemampuan kognitif berpikir simbolik sebelum dan sesudah intervensi. Analisis data dilakukan menggunakan SPSS, termasuk uji t berpasangan dan uji t tidak berpasangan. Hasil penelitian menunjukkan bahwa terdapat peningkatan signifikan dalam literasi keuangan dan kemampuan kognitif berpikir simbolik pada kelompok eksperimen dibandingkan dengan kelompok kontrol. Rata-rata skor literasi keuangan pada kelompok eksperimen meningkat dari 56,78 menjadi 76,45, sedangkan pada kelompok kontrol hanya meningkat dari 57,12 menjadi 60,89. Peningkatan ini signifikan berdasarkan uji t berpasangan (p < 0,05) dan uji t tidak berpasangan (t = 4,56, p < 0,05). Demikian pula, rata-rata skor kemampuan kognitif berpikir simbolik pada kelompok eksperimen meningkat dari 58,34 menjadi 80,23, sementara pada kelompok kontrol hanya meningkat dari 58,67 menjadi 62,45. Peningkatan ini juga signifikan berdasarkan uji t berpasangan (p < 0,05) dan uji t tidak berpasangan (t = 5,34, p < 0,05). Berdasarkan penelitian ini menunjukkan bahwa kegiatan market day efektif dalam meningkatkan literasi keuangan dan kemampuan kognitif berpikir simbolik anak-anak usia 5-6 tahun. Sehingga, kegiatan ini disarankan untuk diintegrasikan ke dalam kurikulum pendidikan anak usia dini. Penelitian lebih lanjut diperlukan untuk mengeksplorasi dampak jangka panjang dan efektivitas kegiatan ini pada kelompok usia yang berbeda.